Differences in Abuse, Neglect, and Exposure to Community Violence in Adolescents With and Without PTSD and Depression. Issue 21 (November 2019) - Nöthling, Jani; Suliman, Sharain; Martin, Lindi; Simmons, Candice; Seedat, Soraya
South African adolescents are exposed to high levels of violence and trauma, including community violence, abuse, and neglect. Violence and trauma are associated with negative mental health outcomes, including posttraumatic stress disorder (PTSD) and depression. Demographic characteristics, additional exposure to trauma, community violence, and types of childhood abuse and neglect may place adolescents at greater risk of developing PTSD. This study aimed to first assess the weighted contribution of demographic factors, trauma load, community violence, and types of abuse and neglect in predicting PTSD symptom severity. Second, we aimed to determine group differences in demographic factors, trauma load, community violence, and types of abuse and neglect among participants with no disorder, PTSD only, PTSD and depression, and depression only. Participants were 215 adolescents identified with emotional and/or behavioral problems and referred to an adolescent trauma clinic from schools in the Western Cape region of South Africa. Clinical assessments were undertaken to assess community violence exposure; physical, sexual, and emotional abuse; physical and emotional neglect; and a clinical diagnosis of PTSD and comorbidity. Trauma-exposed adolescents with PTSD and depression reported significantly higher levels of emotional abuse and community violence exposure in comparison with trauma-exposed adolescents without a disorder. Emotional abuse, community violence exposure, and female gender were significant predictors of PTSD in regression analysis. These findings underscore the contribution of different types of trauma in the development of PTSD. Interventions focused on preventing trauma, PTSD, and depression should be multifaceted and be targeted at various levels, for example, individual/interpersonal level (reduce abuse in the household and immediate environment) and community/societal level (reduce crime rates in communities and strengthen conviction policies). Traumatized youth should routinely be screened for a history of abuse and particularly exposure to community violence, given their strong association with PTSD.